Strategic Subsidies for Green Goods - Carolyn Fischer (Fondazione Eni Enrico Mattei (FEEM), 2016)
Globally and locally, government support policies for green goods (like renewable energy) are much more popular internationally than raising the cost of bads (as through carbon taxes). These support policies may encourage downstream consumption (renewable energy deployment) or upstream development and manufacturing of those technologies. The use of subsidies—particularly upstream ones—is disciplined by World Trade Organization agreements, and its subsidies code lacks exceptions for transboundary externalities like human health or resource conservation, including those related to combating global climate change. The strategic trade literature has devoted little attention to the range of market failures related to green goods. This paper considers the market for a new environmental good that when consumed downstream may provide external benefits like reduced emissions. The technology is traded internationally but provided by a limited set of upstream suppliers that may operate in imperfect markets, such as with market power or external scale economies. We examine the national incentives and global rationales for offering production and consumption subsidies in producer countries, allowing that some of the downstream market may lie in nonregulating third-party countries. Although technology producer countries can benefit from restraints on upstream subsidies, global welfare is higher without them, and market failures imply that optimal subsidies are even higher. We supplement the analysis with numerical simulations of the case of renewable energy, exploring optimal subsidies for the major renewable energy producing and consuming regions and the cost of restrictions on upstream subsidies.
Keywords: F13; F18; H21; Q5; 330; International Trade; Subsidies; Imperfect Competition; Externalities; Emissions Leakage